Viewing the animal: De-ontologizing the anthropology of otherness - García Labrador, Julián; Vinolo, Stéphane (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2022)
Contemporary anthropology has experienced an ontological turn and therefore a reconfiguration of many of its concepts. Yet the authors show that because ontology keeps thinking otherness as a category, the limits of alterity cannot be extended as far as they should. Through the phenomenology of Jean-Luc Marion, it is possible to think otherness and its counter-intentionality not as a type of phenomenon, always already limited because of its constitution by a transcendental subject, but as a possible interpretation of any phenomenon, as long as the subject accepts its givenness. Thus, otherness does not have to be described but declared.